UJI PERTUMBUHAN BIBIT KELAPA SAWIT DURA DAN VARIETAS UNGGUL DXP SIMALUNGUN ( Elaeis guinensis jacg) TERHADAP PUPUK ORGANIK CAIR DI MAIN NURSERY - Hadriman Khair; Darmawati J.S; Romi Saputra Sinaga (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This study aims to determine the effect Dura Oil Palm Seedlings Growth and Variety DXP Simalungun ( Elaeis guineensis Jacq. ) Against Liquid Organic Fertilizer in the Main Nursery by using Plots Separated ( RPT ) design which the main plot is varieties V1 and V2 = DXP Simelungun Dura varieties . Subplot factor is liquid organic fertilizer ( G ) are G1 = 1 ml / liter of water , G2 = 3 ml / liter of water , G3 = 5ml/liter water . There are 6 combination treatment was repeated 3 times resulted in 18 experimental units . The number of plants per plot 5 sample plants with 3 plants , 90 plants total number of plants with a total sample of 54 plants